The German Word “Wohl” in the Novel “Das Parfum” by Patrick Süskind and its Translation in Indonesian - Fadhaly Ijlal Rifqi; Iman Santoso (Universitas Negeri Malang, 2022)
This study aims to describe the form of the equivalent in the Indonesian of the German word “wohl” contained in the novel das Parfum and the function of the German word “wohl” in the novel das Parfum and its equivalent in Indonesian. This research is qualitative descriptive research. The object of this study is all the utterances containing the German word “wohl” in the novel das Parfum by Patrick Süskind. The source of the data was obtained from the novel das Parfum and its translation in Indonesian. Data collection is carried out by read-record technique. This research instrument is the researcher himself (human instrument). To determine the validity of the research data, Expert Judgement is used. The results of this study are concluded that the German word “wohl” in the novel “das Parfum” is used as particle, no equivalent, adverb, adjective, verb, and conjunction.